PENGARUH FAKTOR INTERNAL PERUSAHAAN TERHADAP PROFITABILITAS PERUSAHAAN ASURANSI JIWA DI INDONESIA - Faustinus Wirasadi; Hendrian; Ami Pujiwati (Jurnal Manajemen, 2023)
The influence of foreign ownership on company performance and the influence of company internal factors on the profitability of companies have been widely studied by many researchers. In 2020, the conventional life insurance business consisted of 23 joint venture life insurance and 30 national private life insurance companies. Even though there are fewer in number, joint venture life insurance companies have larger assets and can make a profit, while national private life insurance companies have smaller assets and record losses. All conventional life insurance companies are influenced by the same external company factors, for example economic, demography and regulatory factors. Therefore, a research on the influence of internal company factors on company performance is becoming important. This study uses published financial reports from 16 joint venture life insurance companies and 16 national private life insurance companies for the period 2016 to 2020. The internal factors studied are size (assets), equity, age, liquidityu, tangibility, leverage and loss ratio. The data was processed using panel data regression analysis. Size (assets), equity, liquidity, and loss ratio do not have a significant effet on profitability, both in joint venture life insurance companies and in national private life insurance companies. Company age has a positive and significant effect on profitability of joint venture life insurance companies but does not have a significant effect on national private life insurance companies. Meanwhile, tangibility and leverage have a negative and significant effect on the profitability of national private life insurance companies but do not have significant effect on joint venture life insurance companies.